The political ecology of the state - Ioris, Antonio Augusto Rossotto., author.
1 online resource (ix, 185 pages)
Keywords: "The contemporary state is not only the main force behind environmental change, but the reactions to environmental problems have played a crucial role in the modernisation of the state apparatus, especially because of its mediatory role. The Political Ecology of the State is the first book to critically assess the philosophical basis of environmental statehood and regulation, addressing the emergence and evolution of environmental regulation from the early 20th Century to the more recent phase of ecological modernisation and the neoliberalisation of nature. The state is understood as the result of permanent socionatural interactions and multiple forms of contestation, from a critical politico-ecological approach. This book examines the tension between pro- and anti-commons tendencies that have permeated the organisation and failures of the environmental responses put forward by the state. It provides a reinterpretation of the achievements and failures of mainstream environmental policies and regulation and offers a review of the mains philosophical influences behind different periods of environmental statehood and regulation. It sets out an agenda for going beyond conventional state regulation and grassroots dealings with the state, and as such redefines the environmental apparatus of the state"--